The public healthcare crisis : reconsidering the quantification and payment of damages where delictual liability has been imposed against the state for harm arising from medical malpractice - Conradie, Robyn (Stellenbosch : Stellenbosch University, 2025)
Thesis (LLD)--Stellenbosch University, 2025.